Overland Travel & Tours Sdn. Bhd. / Hasweeta Hashnan... [et al.] - Hashnan, Hasweeta; Mazlan, Shazwin Mazlina; Supian, Sharina; Moinser, Siti Norafizah; Ismail, Zarina (2000)
Overland Travel & Tours Sdn. Bhd. is provided package for traveling, transportation services and all information about traveling around Malaysia. Overland Travel & Tours functioned as stimulators to attract local people to travel domestic and also to attract international tourist to travel inbound by providing various interesting packages and other services. This business operates in N0. 28, Jalan Kayang, 01000 Kangar, Perlis.